Optimizing The Accountability Of Zakat Institutions With The Shariah Enterprise Theory Approach: A Systematic Literature Review - Rusli, Urisnawati; Haliah, Haliah; Nirwana, Nirwana (Lembaga Riset Ilmiah, 2024)
This article aims to explore how the application of Shariah Enterprise Theory (SET) can optimize accountability in the performance of zakat institutions. This article uses the Systematic Literature Review (SLR) method as the main approach. The data used in this article uses secondary data obtained from scientific articles. Some sources of scientific articles include Sciencedirect, Google Scholar and ProQuest published between 2019 and 2024 using the keywords accountability, zakat institutions and shariah enterprise theory. The application of the SET principle in zakat management can increase the accountability of zakat distribution institutions both vertically to Allah SWT and horizontally to all humanity and the wider community. This study shows that the application of SET can bring significant benefits by strengthening the accountability of zakat distribution institutions. The existence of this systematic literature review is expected to be useful for teaching staff and advanced researchers, especially as a suggestion for the development of zakat accountability research with the SET approach in the future. This expectation is in line with the litimation in this study regarding the lack of literature that directly links the implementation of SET in optimizing accountability in zakat institutions.